Telepractice in the System of Providing Correctional and Developmental Services to Children with Speech Disorders: Interaction at a Distance - Mytsyk, Anna; Pryshliak, Mykhailo (Journal of History Culture and Art Research, 2020)
The article is devoted to the problem of optimizing the process of providing correctional and developmental services to children with special needs education in the conditions of significant territorial distances. The study outlines Ukraine’s achievements in introducing inclusive education in the country, creating conditions for children with special educational needs to receive quality educational and correctional services, including in educational institutions that are most accessible and close to their residency. It is noted that children with speech disorders make up a significant share among them. Emphasis is placed on the difficulties of receiving correctional and developmental services by such children in rural areas, especially in remote settlements. Taking into account the experience of foreign colleagues, the available legal documents reflecting the consensus developed by all countries of the world on future directions of education for people with special needs education, in the article sets out its vision for their partial solution through the use of speech therapy assistance telepractice. The article formulates and presents the author’s definition of "telepractice", which means a teacher-speech therapist providing correctional and developmental services using information and communication technologies to accompany and support children with speech disorders and their parents in significant territorial distances. The main advantages of this form of work are substantiated, the specifics of realization of remote interaction models are covered, the expediency of their association for qualitative estimation, diagnostics, correction, and speech development’s monitoring of the child is proved. The problems that hinder the introduction of telepractice in Ukraine, the ambiguous attitude of speech therapists to it are pointed out.